ENHANCING FIFTH GRADERS’ VOCABULARY MASTERY THROUGH SCRIPTED SONGS AT SD NEGERI 16 KESIMAN, DENPASAR TIMUR - I Gusti Ayu Agung Cahyani Pratiwi; Trisnadewi, Komang; Trisna Dewi, Komang (Yavana Bhasha : Journal of English Language Education, 2026)
This Classroom Action Research aimed to investigate how the use of scripted songs can improve vocabulary mastery among fifth-grade students at SD Negeri 16 Kesiman, Denpasar Timur. The research question formulated in this study was: How to improve vocabulary mastery with the use of scripted songs for students in grade 5 at SD Negeri 16 Kesiman? Accordingly, the objective was to examine and describe the process and effectiveness of using scripted songs to enhance students’ English vocabulary mastery. This study employed Classroom Action Research (CAR) based on the model by Kemmis and McTaggart (1988), conducted in two cycles. Each consists of planning, action, observation, and reflection. The participants were 37 fifth-grade students. Data were collected through pre-tests, post-tests as primary data in each cycle. Observation checklists, interviews, and student feedback forms as supporting data. Scripted songs were specifically designed using wild animal themes and descriptive adjectives, in accordance with the students’ curriculum. The findings demonstrated a significant improvement in students’ vocabulary mastery. The mean score in the preliminary study was 53.9, increasing to 72.8 after Cycle I, and further rising to 85.0 in Cycle II. By the end of the research, all students (100%) successfully achieved the Minimum Completion Criterion (KKM). The use of scripted songs not only improved vocabulary mastery but also fostered a more engaging, confident, and enthusiastic classroom environment. Thus, integrating scripted songs through experiential learning is proven effective in improving young learners’ vocabulary mastery and is recommended for English language instruction in elementary schools.